Behavior of Defective Cast in Place Piles (Journal of Engineering, 2021)
This paper deals with testing defected model piles in the soil in order to study their behavior. In this respect, the results of model pile tests are discussed either geotechnically or structurally according to the type of failure. Two parameters were studied in order to evaluate the general behavior of defective piles. These parameters include the defect location and the defect type for floating and end bearing pile. The results of the experimental work indicated that the critical case for floating pile is seen to be when the defect of (5%) at the first third of the pile length at which the decrease in the bearing capacity is about (21%), while the decrease in the bearing capacity is found to be (14%) and (10%), when the defect is at the middle and the lower third of the pile length, respectively. The decrease in the bearing capacity for floating pile is found to be (31%) and (21%) for void and neck defect, respectively, while the decrease in the bearing capacity for end bearing pile is found to be (43%) and (52%) for void and neck defect, respectively.